Large-scale drug screening in patient-derived IDHmut glioma stem cells identifies several efficient drugs among FDA-approved antineoplastic agents - Dao Trong, Huy Philip; Jungwirth, Gerhard; Yu, Tao; Pusch, Stefan; Unterberg, Andreas; Herold-Mende, Christel; Warta, Rolf (Cells, 2020)
The discovery of the isocitrate dehydrogenase (IDH) mutation in glioma led to a paradigm shift on how we see glioma biology. Difficulties in cultivating IDH mutant glioma stem cells (IDHmut GSCs) resulted in a paucity of preclinical models in IDHmut glioma, limiting the discovery of new effective chemotherapeutic agents. To fill this gap, we used six recently developed patient-derived IDHmut GSC lines and performed a large-scale drug screening with 147 Food and Drug Administration (FDA)-approved anticancer drugs. GSCs were subjected to the test compounds for 72 h in concentrations ranging from 0.0001 to 1 µM. Cell viability was assessed by CellTiterGlo and the induction of apoptosis by flow cytometry with Annexin V/propidium iodide staining. The initial screen was performed with two IDHmut GSC lines and identified seven drugs (bortezomib, carfilzomib, daunorubicin, doxorubicin, epirubicin, omacetaxine, plicamycin) with a substantial antiproliferative activity, as reflected by half maximal inhibitory concentrations (IC50) below 1 µM and maximum inhibitory effects (Emax) below 25%. These findings were validated in an additional four IDHmut GSC lines. The candidate drugs, of which plicamycin and omacetaxine are known to cross the blood brain barrier, were used for subsequent cell death analyses. A significant induction of apoptosis was observed at IC50 values of the respective drugs. In summary, we were able to identify seven FDA-approved drugs that should be further taken into clinical investigations for the treatment of IDHmut gliomas.
Im Titel ist "mut" in IDHmut hochgestellt
Gesehen am 26.08.2020